Achieving optimal tomato production levels using the downstream of production - Zul Azhar; Hasdi Aimon; Elida Elida; Zadrian Ardi (Fakultas Ilmu Pendidikan UNP)
The productivity and sustainability of the tomato agriculture sub-sector is an essential aspect of tomato production. However, the problem that arises during the production period is the decline in the price of tomatoes during the harvest so as not to benefit the farmers, it affects the demotivation of production and environmental damage if not treated properly. Survey of this research was conducted on 100 tomato farmers in Kenayahan Selayo Tanang Bukik Sileh Solok. The data were processed using the production model and agricultural costs to observe the productivity and sustainability of the tomato agricultural sub-sector. The results showed that the input factor still decreased return to scale and productivity in the economy still need to be improved. The cost side is not economically efficient with low variable cost coefficients. Achievement of tomato production level optimally is done by downstream of tomato products. The scheme of this process is designed in the form of Development Planning Model of Environmentally Produced Tomato Center.